Governing Public-Private Partnerships: The Problem of Low-Cost Decisions - Karsten Mause (ZBW – Leibniz Information Centre for Economics, 2019)
In many cases, the expected efficiency advantages of public-private partnership (PPP) projects as a specific form of infrastructure provision did not materialize ex post. From a Public Choice perspective, one simple explanation for many of the problems surrounding the governance of PPPs is that the public decision-makers being involved in the process of initiating and implementing PPP projects (namely, politicians and public bureaucrats) in many situations make low-cost decisions in the sense of Kirchgässner. That is, their decisions may have a high impact on the wealth of the jurisdiction in which the PPP is located (most notably, on the welfare of citizen-taxpayers in this jurisdiction) but, at the same time, these decisions often only have a low impact on the private welfare of the individual decision-makers in politics and bureaucracies. The latter, for example, in many settings often have a low economic incentive to monitor/control what the private sector partners are doing (or not doing) within a PPP arrangement. The purpose of this paper is to draw greater attention to the problems created by low-cost decisions for the governance of PPPs. Moreover, the paper discusses potential remedies arising from the viewpoint of Public Choice and constitutional political economy.
Keywords: D72; D73; H10; H54; H57; H82; K00; L32; L33; L33; 330; Public-Private Partnerships; PPPs; Efficiency; Public Choice; Government Failure; Governance